Pengaplikasian Program VISSIM untuk Manajemen Dampak Lalu Lintas di Kabupaten Bone - Hajriyanti Yatmar; S A Adisasmita; M I Ramli; Mubassirang Pasra (Faculty of Engineering UNHAS, 2021)
The technology of transportation is able to support the performance and optimization in unraveling congestion problems. Transportation problems with complexity due to economic growth will require supporting facilities with transportation access. The road network is needed to be able to connect the location from origin to destination arising from generation and attraction. The movement of the trip is affecting the traffic arround. One of anticipation process is developing areas with a study on traffic impact analysis (andallin). Andalallin which is specific study assessing the impact caused by the generation or attraction of an area, potential hazards and accidents, and recommendations related to efforts to deal with impacts on development plans. Every plan for the development of activity centers, settlements, and infrastructure that will cause disturbances in security, safety, order, and smooth traffic and road transportation must be carried out with a Andalallin. Andalalin is able to calculate the trip generation that requires traffic engineering and traffic management to overcome the impact. The existence of a certain area/activity development is part of the transportation system that will create travel potential on building construction. This provides the influence or impact on the surrounding traffic conditions. Visualization for the condition of the road network in 3D through the Vissim program is usually used, the level of road service also shown on the program by entering the parameters from the road geometric condition survey. This traffic simulation is then very important to the stakeholder of transportation caused showing the condition that similar to the real situation with simulation. One of the implementation of Andalallin is traffic management for the construction plan of Bone Tower building in Bone Regency, South Sulawesi.